Real Time Door Unlocking System using Facial Biometrics based on IoT and Python - Krishna, Medisetti Yashwanth Sai; Arya, Anoop; Ansari, Shaziya; Awasya, Simran; Sushakar, Jatoth; Uikey, Neeraj (IEEE International Students' Conference on Electrical, Electronics and Computer Science (Online), 2023)
Traditional locking system like key locks are easily duplicated, thus security of the possessions remains to be a threat. With Artificial Intelligence (AI) proving itself to be robust and accurate, implementing the recent advancements in the field of AI, facial recognition is the latest solution to the problem. The paper discusses a unique methodology of training the facial models for door unlocking system using one of the finest algorithms, Local Binary Pattern Histogram (LBPH) integrated with Internet of Things (IoT) technology to create a functional device that can be mounted on doors. The novelty of the research is that a person only has to look into the camera while the required authentication and unlocking mechanism are done by the device. The door unlocks only when the face is authenticated with a preregistered face whereas a mail with the image of the intruder will be sent to the owner if the faces do not match.